2014
DOI: 10.1097/scs.0000000000000564
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Features of Metopic Suture in Adult Dry Skulls

Abstract: The metopic suture (MS) lies on the midline of the forehead and extends from the frontal bone to the root of the nose. The aim of the current study was to evaluate morphologic features of the complete and incomplete MSs of skulls in the West Anatolian population and rates of the suture types. One hundred sixty crania of West Anatolian people with unknown ages and sex belonging to the anatomy department laboratory of Dokuz Eylül University Medical School were examined. When the MSs that extend from the nasion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…). This variations in shape are similar to the shapes observed by Murlimanju et al, of Indian skulls studied[22], Aksu et al, of Turkish West Anatolian skulls studied[33] and Castilho et al, of Brazilian skulls studied[15]. Variations like H-shaped, Y-shaped and inverted 'U-shaped'…”
supporting
confidence: 87%
“…). This variations in shape are similar to the shapes observed by Murlimanju et al, of Indian skulls studied[22], Aksu et al, of Turkish West Anatolian skulls studied[33] and Castilho et al, of Brazilian skulls studied[15]. Variations like H-shaped, Y-shaped and inverted 'U-shaped'…”
supporting
confidence: 87%
“…The MS may reside as a partial pattern or a complete pattern. The partial patterns expand upward from the nasion or downward from the bregma, different from the completes spanning from the bregma to the nasion [11,24,25]. The suture forms from the bregma and performs toward the nasion.…”
Section: Discussionmentioning
confidence: 95%
“…The incidence of the persistent metopic suture, reported by previous studies, was found to be 1.8% in Lebanese, 3.3% in British, 7.5% in Northeastern Thai, 7.0 -9.7% in Brazilian, 2.0 -85.0% in Indian subpopulations, 11.5% in Nepalese, 35.0% in Nigerians, and 3.3 -75.0 % in Anatolian. The incomplete type is more commonly found than the complete type (Berry, 1975;Ajmani et al, 1983;Baaten et al, 2003;Bilodi et al, 2003;Castilho et al, 2006;Eroğlu, 2008;Hussain Saheb et al, 2010;Manalgiri et al, 2010;Yadav et al, 2010;Chandrasekaran and Shastri., 2011;Murlimanju et al, 2011;Chakravarthi and Venumadhav, 2012;da Silva et al, 2013;Nallathamby et al, 2013;Masih et al, 2013;Pilli and Sunder, 2013;Aksu et al, 2014;Khandare et al, 2014;Kumar and Rajasekar, 2014;Saikia 2014;Santhosh et al, 2014;Wadekar et al, 2014;Arumugam and Arrchana, 2015;Basha and Sugavasi, 2015;Khamanarong et al, 2015;Kumar and Rajshekar, 2015;Hemalatha and Rao, 2016;Nayakanati et al, 2016;Kundu et al, 2017. Shrestha et al, 2017Singh et al, 2017).…”
Section: Discussionmentioning
confidence: 99%